On the Accuracy of Reconstructing Plasma Sheet Electron Fluxes From Temperature and Density Models. Issue 12 (19th December 2019) - Dubyagin, S.; Ganushkina, N.; Liemohn, M.
Abstract: The particle simulations of the inner magnetosphere require time‐dependent boundary conditions for the particle flux set in the transition region between dipolar and tail‐like configurations. Usually, the flux is reconstructed from particle density and temperature predicted by empirical models or magnetohydrodynamic simulations. However, this method requires assumptions about the energy spectra to be made. This uncertainty adds to the inaccuracy of the empirical models or magnetohydrodynamic predictions. We use electron flux measurements in the nightside at r =6–11 R E in the 1–300 keV energy range to estimate the potential accuracy of the electron flux reconstruction from the macroscopic plasma parameter models. We use kappa and Maxwellian distribution functions as well as two population approximations to describe the electron spectra. It is found that this method works reasonably well in the thermal energy range (1–10 keV). However, the average difference between measured and predicted fluxes becomes as large as 1 order of magnitude at energies ≥40 keV. The optimal value of the kappa parameter is found to be between 3 and 4, but it depends strongly on magnetic local time and radial distance. We conclude that the development of the flux‐based models (model of differential flux at several reference energies) instead of density and temperature models can be considered as a promising direction. Key Points: Usage of a standard distribution function, like a single Maxwellian, to reconstruct plasma sheet electron fluxes is only good below 10 keV A kappa, and in some cases two population distributions, gives a better fit, with the kappa parameter strongly depending on location The error with observed fluxes can be large, implying that a more advanced model is needed, based on flux instead of distribution moments